Acompañamiento familiar y logros de aprendizaje en el área de personal social en estudiantes del sexto grado de primaria de la Institución Educativa Claverito del Distrito de Iquitos en el año 2023 - Tamani Cachique, Geni (2024)
Objective: Determine the relationship that exists between family support and the achievement of learning in the area of social personnel in sixth grade primary school students of the Claverito Educational Institution of the Iquitos district, during the 2023 school year. Materials and methods: The research design was non experimental, field, correlational and transectional. The population and sample were 143 students. The data collection instruments were a questionnaire and an evaluation sheet. It was observed that: there is a significant relationship between family support and learning achievement. Very high positive correlation (correlation coefficient of 0.932 and a p value of 0.000). Conclusion: students with a high level of family support reached the "Expected" level of learning, while those with low and medium levels of support were located at the "Start" and "Process" levels, respectively.